The Effect of the Soft Tissue Structures Injury on the Development of Shoulder Joint Arthrosis - Strafun, S.S.; Bohdan, S.V.; Serhiienko, R.O.; Lieskov , V.H. (TERRA ORTHOPAEDICA, 2020)
Summary. Injury of the soft tissue structures of the shoulder joint (rotator cuff, scapula labrum, etc.) is a common cause of omarthrosis. Objective: to investigate the changes in the articular cartilage of the shoulder head and the scapula glenoid in case of the soft tissue structures of the shoulder joint injury. Materials and Methods. We studied the long-term results of conservative and surgical treatment of 330 patients with soft tissue injuries of the shoulder joint, who were treated in the SI “Institute of Traumatology and Orthopedics of NAMS of Ukraine” (Kyiv) from 2009 to 2019. The age of patients ranged from 27 to 68 years (mean age 42.7±19.5 years); 225 were males (68.2%) and 105 females (31.8%). Surgical treatment was performed in 160 patients (48.5%); 170 patients (51.5%) underwent conservative treatment. For evaluation of the influence of the shoulder soft tissue structures injury on the articular cartilage, the degree of the articular cartilage damage was determined by R. Outerbridge and the obtained data were compared with the period from the onset of the disease to surgery. Conclusions: 1. The largest number of secondary omarthroses develops after ruptures of the rotator cuff tendons, both in conservative and surgical groups. Thus, a rupture of rotator cuff tendons is the most arthrosogenic factor among all soft tissue pathology of a shoulder joint. 2. Another arthrosogenic factor for the shoulder joint is rupture of the glenoid labrum in the anterior-inferior part in case of anterior shoulder dislocation and rupture of the posterior glenoid labrum without posterior dislocation (unrealized posterior instability), probably due to high energy trauma and trophic disorders of humeral head after dislocation. 3. A weak but significant dependence was found of the effect of the time from the beginning of the disease to surgery in various Pulley lesions on the degree of damage to the articular cartilage according to R. Outerbridge (r=0.4; p<0.05). Thus, early diagnosis and surgical treatment of Pulley lesions is a major prevention of omarthrosis. 4. A weak but significant dependence of the influence of the period from the onset of the disease to surgery was revealed in patients with isolated injury of the supraspinatus tendon (r=0.38; p<0.05). Early diagnosis and surgical treatment of rotator cuff tendon injuries is the main prevention of omarthrosis.